2001
DOI: 10.1182/blood.v97.8.2333
|View full text |Cite
|
Sign up to set email alerts
|

Echicetin, a GPIb-binding snake C-type lectin from Echis carinatus, also contains a binding site for IgMκ responsible for platelet agglutination in plasma and inducing signal transduction

Abstract: Echicetin, a heterodimeric snake C-type lectin from Echis carinatus, is known to bind specifically to platelet glycoprotein (GP)Ib. We now show that, in addition, it agglutinates platelets in plasma and induces platelet signal transduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 31 publications
(23 reference statements)
3
47
1
1
Order By: Relevance
“…Washed human platelets were collected as described (23). With continuous stirring at 1100 rpm, washed platelets were preincubated with CaCl 2 and MgCl 2 before adding the platelet stimulus, collagen, in the absence or presence of different venom proteins (flavocetin-A and rhodocetin) or antithrombotic drugs (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Washed human platelets were collected as described (23). With continuous stirring at 1100 rpm, washed platelets were preincubated with CaCl 2 and MgCl 2 before adding the platelet stimulus, collagen, in the absence or presence of different venom proteins (flavocetin-A and rhodocetin) or antithrombotic drugs (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…PolyScreen PVDF membranes were from PerkinElmer Life Sciences (Zaventem, Belgium). Echicetinspecific IgM was prepared as previously described (15). Polyvinyl alcohol (30 -70 kDa, Sigma)-based microscope slide mounting medium was prepared by adding 2.4 g to 6 ml of water and stirring for a few hours.…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that cross-linking GPIb by the snake C-type lectin echicetin using IgM is a practical approach to the specific activation of platelets via GPIb (15). The use of echicetin as ligand avoids two complications of VWF, the requirement for shear to induce (VWF)/GPIb binding as well as VWF/␣ IIb ␤ 3 interactions following platelet activation.…”
mentioning
confidence: 99%
“…It was already known that Dami cells express amounts of GPVI adequate to respond to convulxin (19). Ophioluxin gave a strong calcium signal compared with convulxin when the same amounts were used.…”
Section: Fig 3 Ophioluxin Binds Mainly To Gpvimentioning
confidence: 90%
“…Some inhibit the function of platelets by preventing ligand binding, others activate platelets either directly via receptors or indirectly using plasma proteins. Examples of these are echicetin, which uses IgM (19), or botrocetin and bitiscetin that bind von Willebrand factor (20,21). Earlier, these proteins were thought to activate or inhibit platelets via only one receptor.…”
mentioning
confidence: 99%